2007
DOI: 10.1016/j.aquaeng.2006.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Design criteria for rotating flow cells in rectangular aquaculture tanks

Abstract: This work analyzes the simplest inlet and outlet configurations that create homogeneous rotating flow cells in rectangular aquaculture tanks, in order to combine the advantages of rectangular and circular tanks. All the configurations analyzed had a single jet discharge per rotating flow cell, with the drain placed in the center of each rotating flow cell. Length/width ratios (L/W) of 0.95, 1.43 and 1.91 were tested. In addition, the effect of placing oblique baffles in the walls to redirect the water currents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 20 publications
(25 reference statements)
2
23
0
Order By: Relevance
“…Hydrodynamic conditions within various designs of aquaculture tanks and cages have been measured or simulated in order to both optimize and characterize various designs; however, fish were generally not present during these tests (Jeong, Chung, Kim, Choi, & Bae, 2004;Labatut, Ebeling, Bhaskaran, & Timmons, 2007;Oca & Masaló, 2007, 2013Timmons, Summerfelt, & Vinci, 1998;Zhao et al, 2013). Other studies have shown that fish can have an effect on hydrodynamic conditions in both tanks and cages.…”
Section: Introductionmentioning
confidence: 97%
“…Hydrodynamic conditions within various designs of aquaculture tanks and cages have been measured or simulated in order to both optimize and characterize various designs; however, fish were generally not present during these tests (Jeong, Chung, Kim, Choi, & Bae, 2004;Labatut, Ebeling, Bhaskaran, & Timmons, 2007;Oca & Masaló, 2007, 2013Timmons, Summerfelt, & Vinci, 1998;Zhao et al, 2013). Other studies have shown that fish can have an effect on hydrodynamic conditions in both tanks and cages.…”
Section: Introductionmentioning
confidence: 97%
“…Placing these types of structures in hatchery tanks can be problematic because they may trap food and feces, increase disease risk, or interfere with the hydraulic self‐cleaning that is inherent to circular tanks (Tvinnereim and Skybakmoen ; Baynes and Howell ; Timmons et al. ; Tuckey and Smith ; Oca and Masalo , ; Krebs et al. ).…”
mentioning
confidence: 99%
“…Oca and Masaló [15] evaluated the width-to-length ratio in the formation of dead volumes. Evaluations using particle tracking velocity (PTV) techniques indicate that a single water inlet in a rectangular tank provides more areas with dead volumes [16].…”
Section: Resultsmentioning
confidence: 99%